Comparing Upper Limb Performance Between Women and Men in CrossFit: Associations with FMS, Davis, and Dash Tests - Sabikeh Moghaddamnezhad; Abdolrasoul Daneshjoo (Islamic Azad University, Hamedan Branch, 2024)
Objective The current study aimed to compare the upper limb performance (range of motion and Y balance test) of male and female CrossFit athletes and its relationship with scores from the functional movement screen (FMS), Davis test, and Dash test. Methods Forty-two male and female CrossFit athletes were included in this study based on specific criteria. Measurements were taken for internal and external rotation range of motion, right and left Y balance tests, FMS scores, Davis test results, and the degree of shoulder and hand functional disability (DASH). The normality of the data was assessed using the Shapiro-Wilk test. As the data were not normally distributed, Spearman's correlation coefficient was used to examine the relationships between variables. Additionally, the Mann-Whitney U test was employed to compare groups of men and women. Results The findings revealed a significant positive correlation between external and internal rotation range of motion and the Y balance test of the right and left hands with FMS and Davis test scores in men (p ≤ 0.05). However, there was no significant relationship between external and internal rotation range of motion and the Y balance test of the right and left hands with Dash test scores (p > 0.05). For women, a significant positive correlation was observed between external and internal rotation range of motion and the Y balance test of the right and left hands with the FMS test (p ≤ 0.05). Additionally, a positive correlation was found between internal rotation range of motion and the Y balance test of the left hand with the Davis test (p ≤ 0.05). Statistical analysis revealed significant differences between men and women in external rotation range of motion, Davis test, and Dash test results (p ≤ 0.05). However, no significant differences were observed between men and women in other variables (p > 0.05). Conclusion Based on the study results and the relationship between FMS and Davis test scores with range of motion and Y balance test performance in male and female CrossFit athletes, these tests can be utilized to assess potential injury risk and predict injury likelihood in this population.